Effect of stocker management program on beef cattle skeletal muscle growth characteristics, satellite cell activity, and paracrine signaling impact on preadipocyte differentiation - Mathew A. Vaughn; Phillip A. Lancaster; Kelly C. Roden; Evin D. Sharman; Clinton R. Krehbiel; Gerald W. Horn; Jessica D. Starkey (Journal of Animal Science and Technology, 2019)
The objective of this study was to determine the effect of different stocker management programs on skeletal muscle development and growth characteristics, satellite cell (SC) activity in growing-finishing beef cattle as well as the effects of SC-conditioned media on preadipocyte gene expression and differentiation. Fall-weaned Angus steers (n = 76; 258 ± 28 kg) were randomly assigned to 1 of 4 stocker production systems: 1) grazing dormant native range (NR) supplemented with a 40% CP cottonseed meal-based supplement (1.02 kg · steer−1 · d−1) followed by long-season summer grazing (CON, 0.46 kg/d); 2) grazing dormant NR supplemented with a ground corn and soybean meal-based supplement fed at 1% of BW followed by short-season summer grazing (CORN, 0.61 kg/d); 3) grazing winter wheat pasture (WP) at high stocking density (3.21 steers/ha) to achieve a moderate rate of gain (LGWP, 0.83 kg/d); and 4) grazing winter WP at low stocking density (0.99 steers/ha) to achieve a high rate of gain (HGWP, 1.29 kg/d). At the end of the stocker (intermediate harvest, IH) and finishing (final harvest, FH) phases, 4 steers / treatment were harvested and longissimus muscles (LM) sampled for cryohistological immunofluorescence analysis and SC culture assays. At IH, WP steers had greater LM fiber cross-sectional area than NR steers; however, at FH, the opposite was observed (p < 0.0001). At IH, CORN steers had the lowest Myf-5+:Pax7+ SC density (p = 0.020), while LGWP steers had the most Pax7+ SC (p = 0.043). At FH, CON steers had the highest LM capillary density (p = 0.003) and their cultured SC differentiated more readily than all other treatments (p = 0.017). At FH, Pax7 mRNA was more abundant in 14 d-old SC cultures from HGWP cattle (p = 0.03). Preadipocytes exposed to culture media from proliferating SC cultures from WP cattle isolated at FH had more PPARγ (p = 0.037) and less FABP4 (p = 0.030) mRNA expression compared with NR cattle. These data suggest that different stocker management strategies can impact skeletal muscle growth, SC function, and potentially impact marbling development in growing-finishing beef cattle.